Statistical bioinformatics with R - Sunil K Mathur (Academic Press/Elsevier, 2010)
Provides coverage of complex statistical methods in context with applications in bioinformatics. This book integrates biological, statistical and computational concepts. It includes R & SAS code. It presents Bayesian methods and the modern multiple testing principles.